PEMANFAATAN TEKNOLOGI INFORMASI UNTUK MENDORONG PERCEPATAN PENYELESAIAN PERKARA DI MAHKAMAH AGUNG - Asep Nursobah (Jurnal Hukum dan Peradilan, 2015)
Utilization of information technology by Supreme Court is to boost the eficiency and effectivity the resolution of the case, but in fact the Utilization of information technology still focus on electronic record only, the technology hasn’t been optimalized yet to improve the performance of judiciary institution.Keywords: Information Technology, Cases Settlement, Supreme Court